Goddess girls. 4, Artemis the brave - Holub, Joan; Campiti, David; Williams, Suzanne, 1953- (Campiti, David. Goddess girls graphic novel, 2023)
While protecting egotistical transfer student Orion, Artemis makes a mistake that later provides her with the chance that she has both hoped for and dreaded, to prove her courage to herself and others at Mount Olympus Academy.